Regulation and protection of personal health data in the AI era: international experience - N. M. Galkina; D. V. Kuznetsova (Теоретическая и прикладная юриспруденция)
Artificial intelligence is actively taking over sphere after sphere and particular successes and achievements can be seen in the medical sector and medical technology. However, the introduction of AI raises a number of practical and ethical issues. One of the main ones is the issue of handling personal data, as access to a large number of patients’ health data plays a key role in the development and use of AI in medicine. The most convenient solution for their use is to anonymise them beforehand. However, with anonymisation, there is a risk of re-identification and the potential for loss of data informativeness may be lost. In the framework of this article the experience in the sphere of legal regulation of personal health data handling when using artificial intelligence systems in medicine is considered in the example of the USA, EU and Singapore. Each country is endeavoring to strike a balance between the protection of personal data privacy and the advancement of technological innovations. The analysis suggests that the emphasis on artificial intelligence development necessitates specific premises in the domain of personal data protection. Conversely, stringent standards for the protection of personal data could potentially exert a restrictive influence.